An Empirical Study on Green Consumerism among College Students of Mumbai with Respect to Electric Vehicles (London Journal of Research In Humanities and Social Sciences, 2025)
This study investigates the attitudes, perceptions, and purchase intentions towards electric vehicles (EVs) among college students in Mumbai, a demographic crucial to the future of sustainable consumption. A quantitative approach was employed, utilizing a structured questionnaire distributed to a sample of 312 students across various colleges in Mumbai. The findings reveal a strong environmental consciousness (Mean=4.42) and a positive attitude towards EVs as a symbol of modernity (Mean=4.05). However, a significant intention-behavior gap exists. The primary barriers to adoption are high purchase cost (72.1%), perceived lack of charging infrastructure (68.3%), and range anxiety (55.4%). While government subsidies are seen as a key motivator (65.7%), awareness of existing policies remains moderate. The study concludes that while Mumbai's youth are ideologically aligned with green consumerism, practical and economic barriers hinder the translation of intention into purchase behavior. Recommendations include enhanced policy communication, targeted educational campaigns, and infrastructure development focused on academic institutions.
Keywords: identity; sign; literary semiotics; Trauma; posttraumatic stress disorder